ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI TERHADAP PEMILIHAN KARIR SEBAGAI KONSULTAN PAJAK (Studi Kasus Pada Mahasiswa S1 Akuntansi Universitas Pasir Pengaraian) - Venny Rahmania,; Nurhayati,; Arma Yuliza, (AKPEM : Jurnal Akuntansi Keuangan Dan Akuntansi Pemerintahan, 2021)
This study aims to analyze the factors that influence the interest of accounting students in choosing a career as a tax consultant. The research method used is qualitative research which is changed to quantitative research. The sample used in this study was 106 respondents who were taken by purposive sampling method with certain criteria. The results of this study indicate that the knowledge of tax, finance and motivation variables affect the interest of accounting students in choosing a career as a tax consultant. Meanwhile, career opportunities, self-efficacy and work environment do not affect the interest of accounting students in choosing a career as a tax consultant